Circular RNAs in Embryogenesis and Cell Differentiation With a Focus on Cancer Development - Di Agostino, Silvia; Riccioli, Anna; De Cesaris, Paola; Fontemaggi, Giulia; Blandino, Giovanni; Filippini, Antonio; Fazi, Francesco (Frontiers in Cell and Developmental Biology, 2020)
In the recent years the high throughput sequencing technologies have identified thousands of non-coding RNAs. Among them, circular RNAs (circRNAs) are a well-represented class characterized by the high sequence conservation and cell type specific expression in eukaryotes. They are formed by covalently closed loops through back-splicing. Recently, circRNAs were found to regulate a variety of cellular processes functioning as miRNA sponges, RBP binding molecules, transcriptional regulators, scaffold for protein translation, as well as immune regulators. A growing number of studies are showing that dysregulated expression of circRNAs plays important and decisive actions during the development of several human diseases including cancer. The research on their biogenesis and on the various molecular mechanisms in which they are involved is going very fast; however, there are still few studies that address their involvement in embryogenesis and eukaryotic development. This review has the intent to describe the most recent progress in the study of the biogenesis and the molecular activities of circRNAs providing insightful information in the field of embryogenesis and cell differentiation. In addition, we describe the latest research on circRNAs as novel diagnostic or promising biomarkers in diverse types of tumors.